Regulatory entry barriers, rent-shifting and the home market effect - Martín Tobal (Banco de México, 2016)
I modify a standard model of the home market to introduce entry barriers that create local rents. The existence of rents has relevant implications. First, the home market effect magnifies. Second, when countries are sufficiently unequal in size and rents are sufficiently large, a trade costs reduction reduces the small country's welfare. Third, entry barriers increase the large country's market size and may surprisingly increase its welfare. Fourth, a unilateral increase in import tariffs shifts foreign rents to the home country. This rent shifting effect intensifies the standard production relocation motive for trade policy intervention.
Keywords: F12; F13; 330; Rent Shifting; Home Market Effect; Production Relocation Effect